Transfer of heavy metal along food chain: a mini‐review on insect susceptibility to entomopathogenic microorganisms under heavy metal stress. Issue 3 (9th October 2020) - Jiang, Dun; Tan, Mingtao; Guo, Qingxi; Yan, Shanchun
Abstract: The development and physiological status of pest insects are important factors that affect the effectiveness of biological control. Current knowledge reveals that heavy metals can be transferred to phytophagous insects through food chains and cause various chronic toxicological effects on the growth and physiology of phytophagous insects. These findings potentially attribute heavy metal contamination to an environmental factor governing biocontrol efficiency against pest insects, pointing to an urgent demand to better understand the effects of heavy metal exposure on insect susceptibility to entomopathogenic microorganisms. Here we discuss the transfer characteristics of heavy metals along the food chains to phytophagous insects and conclude that heavy metal exposure may promote insect susceptibility to entomopathogenic microorganisms in the heavy metal‐contaminated regions. Furthermore, we propose a 'combined effect' hypothesis that combination of entomopathogenic agent and heavy metal stress can cause a much higher overall insect mortality than does the entomopathogenic agent or the heavy metal stress alone. This is a new and relatively unexplored area in the microbial‐based biocontrol research, which might have great potential for future optimization of biocontrol strategies against economically and ecologically important agricultural or forest pests in the heavy metal polluted areas. © 2020 Society of Chemical Industry Abstract : Heavy metal contamination is a potential environmental factor affecting the control efficiency of microbial‐based biological control against agricultural and forestry pest insects.